A study on the deviation of apical foramen from the root apex of mandibular first premolars - Faustino, Delfin Manuel D.
Two hundred mandibular first premolars were decalcified, dehydrated, made transparent, and injected with drawing ink to determine the type of root canals, as well as the frequency and direction of deviation of the apical foramen from the anatomic root apex. The frequency of deviation averaged 73%, depending on the type of canal examined. The predominating direction of deviation was also dependent on the type of canal examined.